(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Ensuring the stable work of personnel is an important condition for ensuring the normal operation of the entire organization. In the system of vocational education, this means that the methods of personnel development and the personnel system will reach a new qualitative level.Proper planning, selection and development of personnel in the system of vocational education is the basis of quality education and training. qualified mid-level personnel.